Dialdehydes Lead to Exceptionally Fast Bioconjugations at Neutral pH by Virtue of a Cyclic Intermediate1. (22nd August 2014) - Schmidt, Pascal; Zhou, Linna; Tishinov, Kiril; Zimmermann, Kaspar; Gillingham, Dennis
Abstract One of the open challenges in chemical biology is to identify reactions that proceed with large rate constants at neutral pH values. As shown here, dialdehydes react with O‐alkylhydroxylamines at rates of 500 M−1 s−1 at neutral pH values in the absence of catalysts. The key to these conjugations is an unusually stable cyclic intermediate, which ultimately undergoes dehydration to yield an oxime. The scope and limitations of the method are outlined, as well as its application in bioconjugation and a mechanistic interpretation that will facilitate further developments of reactions with alkylhydroxylamines at low substrate concentrations.